Tsai Ming-Liang and a Cinema of Slowness - Lim, Song Hwee, 1965- (Book collections on Project MUSE., 2014)
How can we qualify slowness in cinema? What is the relationship between a cinema of slowness and a wider socio-cultural slow movement? A body of films that shares a propensity toward slowness has emerged in many parts of the world over the past two decades. This is the first book to examine the concept of cinematic slowness and address this fascinating phenomenon in contemporary film culture. Providing a critical investigation into questions of temporality, materiality, and aesthetics, and examining concepts of authorship, cinephilia, and nostalgia, Song Hwee Lim offers insight into cinematic slowness through the films of the Malaysian-born, Taiwan-based director Tsai Ming-liang. Through detailed analysis of aspects of stillness and silence in cinema, Lim delineates the strategies by which slowness in film can be constructed. By drawing on writings on cinephilia and the films of directors such as Abbas Kiarostami, Hou Hsiao-hsien, and Nuri Bilge Ceylan, he makes a passionate case for a slow cinema that calls for renewed attention to the image and to the experience of time in film.